2022
DOI: 10.2478/remav-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Land Price Regression Model and Land Value Region Map to Support Residential Land Price Management: A Study in Nghe an Province, Vietnam

Abstract: The real estate market in areas with many socio-economic activities needs to be strictly managed due to the difference between the market price of urban land and the price of land set by the state. This study identifies and analyzes the influence of some factors on land prices in peri-urban areas to develop land pricing standards consistent with the price level in Nghe An province. The study surveyed 362 land users and 200 samples of successfully transferred properties in the study area. Based on the multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Additionally, rural workers' use of compensation money has been found to impact their job transition process. In some cases, rural households may invest their compensation funds in building houses, purchasing equipment, or other immediate needs, rather than considering investing in vocational training or exploring alternative career paths (Ha et al, 2022;Tuan, 2021;Tuan & Hegedűs, 2018;Wang et al, 2019). This may limit their ability to effectively transition to new employment opportunities or acquire the necessary skills for non-agricultural occupations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rural workers' use of compensation money has been found to impact their job transition process. In some cases, rural households may invest their compensation funds in building houses, purchasing equipment, or other immediate needs, rather than considering investing in vocational training or exploring alternative career paths (Ha et al, 2022;Tuan, 2021;Tuan & Hegedűs, 2018;Wang et al, 2019). This may limit their ability to effectively transition to new employment opportunities or acquire the necessary skills for non-agricultural occupations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to individual factors, the utilization of compensation money by rural workers also affects their job transition process. Research indicates that some households primarily invest their compensation funds in immediate needs such as housing or purchasing equipment, neglecting vocational training or exploring alternative career paths (Chen et al, 2020;Ha et al, 2022;Tuan, 2021;Tuan & Hegedűs, 2018;Wang et al, 2019). This approach can limit their ability to effectively transition to new employment opportunities or acquire the necessary skills for non-agricultural occupations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Land value prediction is based on NJOP building price, land area, and land price [13]. However, in this study, data collection was carried out by collecting data/samples in the field, using land valuation methods such as market data comparison [7], cost approach, and the income approach. The method used in this research is using a combination of land valuation methods according to the conditions in the field, namely the comparison of market data and the cost approach.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore,(Binoy et al, 2022) found that Land value has a high positive correlation with permissible FAR; When the FAR value is raised by 0.5, the land price rises by 31%. In contrast,(Qu et al, 2020) found that greater FAR means less public space in the community and a lower comfort level for residents (Ha et al, 2022). studied ten independent factors that affect residential land prices in the regression model.…”
mentioning
confidence: 99%